2010
DOI: 10.3329/jhpn.v28i1.4527
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status, Dietary Intake, and Relevant Knowledge of Adolescent Girls in Rural Bangladesh

Abstract: This study estimated the levels and differentials in nutritional status and dietary intake and relevant knowledge of adolescent girls in rural Bangladesh using data from the Baseline Survey 2004 of the National Nutrition Programme. A stratified two-stage random cluster-sampling was used for selecting 4,993 unmarried adolescent girls aged 13–18 years in 708 rural clusters. Female interviewers visited girls at home to record their education, occupation, dietary knowledge, seven-day food-frequency, intake of iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
95
5
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 8 publications
16
95
5
2
Order By: Relevance
“…Then growth in stature continues for up to 7years.In undernourished populations, growth rate during adolescence is slower. 12 Using maximum growth spurt or menarche as an indicator, maturation may be delayed in malnourishedgirls by an average of two years. Maternal stunting is a factor of increased obstetric risk, and it can be attributed to chronic malnutrition.The intervention in our study showed a significant increase in height of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Then growth in stature continues for up to 7years.In undernourished populations, growth rate during adolescence is slower. 12 Using maximum growth spurt or menarche as an indicator, maturation may be delayed in malnourishedgirls by an average of two years. Maternal stunting is a factor of increased obstetric risk, and it can be attributed to chronic malnutrition.The intervention in our study showed a significant increase in height of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary knowledge and access to resources are critical in improving health and nutrition in a sustainable way. It has appeared that knowledge of nutrition among rural adolescent girls is poor and they are generally unaware of the need of consuming healthy quantities of foods such as fish, meat, eggs, milk, vegetables and fruits during pregnancy and lactation [10].…”
Section: Knowledge Of Nutritionmentioning
confidence: 99%
“…Adolescence represents one of the critical transitions in the life span and is characterized by rapid physical growth and changes in body composition, physiology, and endocrine with profound biological, emotional, social, and cognitive changes 1 . During adolescence nutritional and energy needs are increased due to the increased growth rate and changes in body composition associated with puberty 2 .…”
Section: Introductionmentioning
confidence: 99%